2008
DOI: 10.1083/jcb.200709090
|View full text |Cite
|
Sign up to set email alerts
|

Cripto promotes A–P axis specification independently of its stimulatory effect on Nodal autoinduction

Abstract: The EGF-CFC gene cripto governs anterior–posterior (A–P) axis specification in the vertebrate embryo. Existing models suggest that Cripto facilitates binding of Nodal to an ActRII–activin-like kinase (ALK) 4 receptor complex. Cripto also has a crucial function in cellular transformation that is independent of Nodal and ALK4. However, how ALK4-independent Cripto pathways function in vivo has remained unclear. We have generated cripto mutants carrying the amino acid substitution F78A, which blocks the Nodal–ALK4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Finally, using murine knock out models, Liguori and colleagues recently demonstrated that Nodal can signal extensively and control axis specification in the absence of Cripto, if its inhibitor Cerberus is also inhibited [44]. More recent evidence also supports a role for Cripto-1 during anterior-posterior axis specification independently of canonical Nodal signaling pathway [45].…”
Section: Cripto-1mentioning
confidence: 85%
“…Finally, using murine knock out models, Liguori and colleagues recently demonstrated that Nodal can signal extensively and control axis specification in the absence of Cripto, if its inhibitor Cerberus is also inhibited [44]. More recent evidence also supports a role for Cripto-1 during anterior-posterior axis specification independently of canonical Nodal signaling pathway [45].…”
Section: Cripto-1mentioning
confidence: 85%
“…Experimentally, cells in the visceral endoderm may be directed to move from regions of high (where there is elevated cell proliferation) to low Nodal activity (Fig. 5B) (Yamamoto et al, 2004) and, consistent with Nodal having such a role, DVE cells do not move when Cripto activity is lost (Ding et al, 1998 ;Criptonull), allows the formation and translocation of the DVE to become the AVE D'Andrea et al, 2008). AVE formation may therefore be accomplished, at least in part, by a Cripto-independent Nodal pathway that is sensitive to Cer1 inhibition.…”
Section: Cellular and Molecular Mechanisms Of Dve Translocationmentioning
confidence: 99%
“…Compound mutant mouse embryos lacking both Cripto and Cryptic phenocopy Nodal Ϫ/Ϫ null mutants (17). In addition, analysis of Cripto Ϫ/Ϫ and Cryptic Ϫ/Ϫ single mutants revealed unique functions in different tissues: Cripto expression in the epiblast enables Nodal autoinduction and thereby promotes germ layer formation (14,18). By contrast, Cryptic is primarily required after gastrulation to mediate paracrine Nodal signaling from the ventral node to the left lateral plate mesoderm during leftright axis formation (19,20).…”
mentioning
confidence: 99%